Project-Based Learning: Road to Make Connection between Concept and Skills in Mathematics Manipulative Media - Wulandari, Tri Candra; Qamar, Kawakibul (MEJ (Mathematics Education Journal), 2018)
Mathematics is based on certain concepts and rules, teachers must motivatestudents to be able to express the concept in the real world yet. not allmathematical material is abstract or all mathematical material can be madereal. Therefore, there needs to be a bridge between the abstract world andthe real world. Mathematics Manipulative Media is one of the subjects inmathematics education program at Kanjuruhan University. This subjects isgiven to third year students this class started using Project-Based Learning(PBL). PBL was design to teach the student with combining concept andstudent skills. These skills include communication and presentation skills,organization and time management skills, research and inquiry skills, selfassessmentand reflection skills, group participation and leadership skills,and critical thinking. All of these skills are needed for their life in theirsociety. Implementation of PBL in this manipulative media class is doneusing 4 stages, namely the delivery of rules and concepts, the delivery ofideas, product/creation solution and problem conclusion. While the skillsinvolved at each stage are communication and presentation skills, time andorganizational management skills, searching and discovering skills, selfassessingand reflection skills, leadership and lead skills, and criticalthinking.